Health Benefits and Applications of Goji Berries in Functional Food Products Development: A Review - Bojana B. Vidović; Danijel D. Milinčić; Mirjana D. Marčetić; Jelena D. Djuriš; Tijana D. Ilić; Aleksandar Ž. Kostić; Mirjana B. Pešić (MDPI AG, 2022)
Goji berries have long been used for their nutritional value and medicinal purposes in Asian countries. In the last two decades, goji berries have become popular around the world and are consumed as a functional food due to wide-range bioactive compounds with health-promoting properties. In addition, they are gaining increased research attention as a source of functional ingredients with potential industrial applications. This review focuses on the antioxidant properties of goji berries, scientific evidence on their health effects based on human interventional studies, safety concerns, goji berry processing technologies, and applications of goji berry-based ingredients in developing functional food products.